1992
DOI: 10.1111/j.1399-302x.1992.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Avidity and titer of immunoglobulin G subclasses to Porphymmonas gingivalis in adult periodontitis patients

Abstract: The relative avidity and titer of antibodies representing the 4 immunoglobulin G (IgG) subclasses (IgG1-4) reactive with Porphyromonas gingivalis, P. gingivalis-lipopolysaccharide (-LPS), streptokinase (SK) and tetanus toxoid (TT) in the sera of patients having adult periodontitis and of healthy controls were measured. Patient antibody titers to P. gingivalis and P. gingivalis-LPS were found to be significantly elevated for IgG, IgG1 (no P. gingivalis-LPS antibodies) and IgG2. The predominant antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…The data reported here demonstrate that antibody responses to the HtpG subpeptides do not follow the same pattern as do antibodies to whole P. gingivalis cells or other P. gingivalis antigens (11,24,45,48). Also, the P18␣ epitope, especially with normalization to the values for the P18␥ peptide, yields statistically superior relationships to the clinical statuses of periodontitis subjects in comparison to antibodies to the whole P18 peptide.…”
Section: Vol 16 2009 Prediction Of Health In Periodontitis Subjectsmentioning
confidence: 74%
“…The data reported here demonstrate that antibody responses to the HtpG subpeptides do not follow the same pattern as do antibodies to whole P. gingivalis cells or other P. gingivalis antigens (11,24,45,48). Also, the P18␣ epitope, especially with normalization to the values for the P18␥ peptide, yields statistically superior relationships to the clinical statuses of periodontitis subjects in comparison to antibodies to the whole P18 peptide.…”
Section: Vol 16 2009 Prediction Of Health In Periodontitis Subjectsmentioning
confidence: 74%
“…While few studies have investigated porcine antibody and its avidity maturation after infection, IgG2 was revealed to be the most important antibody subclass and it is in direct proportion to the age of individuals according to human antibody avidity studies (Lopatin and Blackburn, 1992;Nair et al, 2007). Thus, the likelihood of porcine mimicry to human antibody avidity traits should be further investigated, since presently whole antibody pool was detected without differentiating its isotypes and regardless of age-dependent avidity factors.…”
Section: Discussionmentioning
confidence: 89%
“…Antibody avidity is an expression of the primary binding activity which forms antigen-antibody complexes [18] and measures the net binding strength of multivalent antigens to polyclonal antibodies. Investigations have estimated the avidity of antibody to Porphyromonas gingivalis in adult periodontitis [12,13] and patients with rapidly progressive periodontitis [14,15]. These studies suggested that low avidity antibody in these patients may be ineffective in clearing P. gingivalis in these periodontal diseases, and that non-surgical therapy could contribute to stimulating the production of higher avidity antibody.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies clearly demonstrated elevations in antibody levels in periodontitis, more recent reports have suggested the need to investigate the functional capabilities of these antibodies [12][13][14][15][16][17]. One approach to describing antibody © 1995 Blackwell Science function is to measure the avidity of the antibody interaction with antigen.…”
Section: Introductionmentioning
confidence: 99%